en - Hutabarat, Dina Yemima Alicia; Durahman, Eva Utami (e-Journal of Linguistics; Vol 16 No 1 (2022): ejl-January, 2021)
This research aims to find, record, and analyze one of the translation techniques, namely Literal Translation from Indonesian to English which contains conceptual meaning in a short film entitled LDR by DPR Production (2019). This research uses descriptive qualitative research method. The method of collecting data for this research is by watching the short film and writing the film script along with the English translation that already exists in the film. The form of the data collected is in the form of sentences containing the Literal Translation technique which also has an understandable conceptual meaning. There are 36 data obtained from 41 sentences in the film. Based on the results of this study, a short film entitled LDR by DPR Production (2019) has a translation technique, namely Literal Translation along with the similarity of meaning in every sentence in the film.